2011
DOI: 10.1007/s12199-011-0212-3
|View full text |Cite
|
Sign up to set email alerts
|

Influences of income and employment on psychological distress and depression treatment in Japanese adults

Abstract: Objectives Psychological distress is a health issue of critical importance, especially in people of working age in developed countries, including Japan. This study examined the relationships of income and employment arrangement with psychological distress and treatment of depression in a national sample of Japanese adults. Methods Data for 10,959 men and 11,655 women 25-59 years of age, obtained from the Comprehensive Survey of the Living Conditions of People on Health and Welfare in 2007, were examined. Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 22 publications
5
43
3
1
Order By: Relevance
“…Moreover, the prevalence of treatment in those with symptoms was very high (RII = 3.82) for the young group. We assessed this relationship between income and depression in a previous study [35]; in addition to vulnerability to psychological distress in the socially disadvantaged population, we speculate that those with high SES might be reluctant to receive health care even if they are experiencing psychological discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the prevalence of treatment in those with symptoms was very high (RII = 3.82) for the young group. We assessed this relationship between income and depression in a previous study [35]; in addition to vulnerability to psychological distress in the socially disadvantaged population, we speculate that those with high SES might be reluctant to receive health care even if they are experiencing psychological discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…66,67 Other predisposing factors to undiagnosed depression include fewer primary care visits (where depression care is usually initiated), [66][67][68] low education (due to higher mental health stigma than in those with more education), 69,70 and being employed (due to workplace stigma and potential income loss). 20,21,71 The negative association between employment and self-reported depression treatment deserves special to 20 weekly 1-hour sessions at sites of care. 72,73 Leaving work for psychotherapy sessions creates a potential for income loss, assuming one only gets paid for hours worked.…”
Section: Study Implicationsmentioning
confidence: 99%
“…The conceptual model and available evidence suggested that patients’ attributes largely determine who receives depression care . Relevant patient attributes include (a) sociodemographic characteristics (ie, race, age, income, educational attainment, employment status, rural or urban residence, and marital status); (b) clinical characteristics (ie, severity of depression, and cancer stage at diagnosis); and (c) other individual‐level characteristics (ie, health insurance coverage Charlson comorbidity index, and number of annual visits to primary care clinics) . After reviewing studies in other patient populations, we hypothesized that age, African‐American race, low education, rural residence, being unmarried, unemployment, and low annual income were negatively associated with depression care among prostate cancer survivors …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emellett a kevésbé fejlett országokban a depresszió előfordulása magasabb. A szegényebb populáció körében magasabb a pszichológiai distressz előfordulása, míg a magasabb bevételű népesség körében alacsonyabb a depresszió kezelésének aránya [4].…”
unclassified